The effect of vertical skeletal proportions, skeletal maturation, and age on midpalatal suture maturation: a CBCT-based study - Martina Ferrillo; Kieran Daly; Nikolaos Pandis; Padhraig S. Fleming (SpringerOpen, 2024)
Abstract Background Midpalatal suture (MPS) maturation may be influenced by a range of parameters including age, gender, and vertical skeletal pattern. We therefore aimed to evaluate the effect of Frankfurt-mandibular angle (FMA), skeletal maturation, and age on the timing of MPS maturation. Methods In this cross-sectional study, cone-beam computed tomography (CBCT) and lateral cephalograms were used to assess the MPS and cervical vertebral maturation (CVM) stage. A proportional odds logistic regression model was used to assess associations between age adjusted for gender and MPS maturation, and a regression analysis was performed to analyze the effect of vertical pattern on these associations. Results A total of 201 patients (84 male and 117 female) with a mean age of 13.48 (SD 1.94) were included. With increasing age, the odds of belonging to a higher maturation stage increased (OR: 2.14; 95% CI 1.789; 2.567; P < 0.001); however, no association between FMA and MPS maturation was observed (OR: 1.01; 95% CI 0.964; 1.051; P = 0.76). A strong correlation between MPS maturation and CVM stage was not reported. Males had a higher probability of belonging to a lower MPS maturation stage (OR: 0.24; 95% CI 0.136; 0.415; P < 0.001). Conclusions Based on this cross-sectional analysis, midpalatal sutural maturation classification is associated with chronological age and occurs later in males. Neither CVM staging nor variation in vertical skeletal proportions were useful predictors of midpalatal maturation stage.